Analisis Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi pada Rumah Sakit Slamet Riyadi - Rehaninditya Annisa Wibowo; Anita Wijayanti; Yuli Chomsatu (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
If the use of an accounting information system is not followed by adequate quality from its users, the accounting information system will not function as it should, even if the most sophisticated system design is used. Such problems arise in the use of information systems among employees at Slamet Riyadi Hospital, Surakarta, especially those related to finance. It can be seen from the above phenomenon that there is still dissatisfaction with the quality of the accounting information system used because employees still have difficulty using it. The type of research used is a quantitative approach. The data source used is primary data. This research was conducted at the Slamet Riyadi Hospital, Surakarta, with the research population being employees in the finance and accounting departments who used information systems with a total of 100 people and the sample for this research was 38 people using Saturated Sampling. The results of this research are that there are factors that have a positive influence on the performance of accounting information systems, namely top management support factors, and user involvement and personal technical abilities do not have a positive influence